Antineutrophil cytoplasmic antibody-associated vasculitis: insights into relapse risk and future management directions - Alberici, Federico; Flossmann, Oliver; Lamprecht, Peter; Loudon, Kevin W.; Padoan, Roberto; Popov, Tamara; Salvarani, Carlo; Mohammad, Aladdin J. (Frontiers in Immunology, 2025)
Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) has a relapsing-remitting course and, even with the availability of effective maintenance therapies such as rituximab, relapse rates remain high. Relapse is associated with the accrual of organ damage stemming from both the underlying disease and from the effects of AAV treatments; thus, early detection and proactive prevention are crucial. AAV study populations typically include mixed cohorts of patients with new-onset and relapsing disease. Although data specifically addressing re-induction of remission after relapse are limited, available evidence suggests high remission rates when rituximab is combined with glucocorticoids. However, the balance between effective disease control and the potential treatment-related side effects must be carefully considered, and new therapeutic options may help improve this tradeoff. The aim of this review is to explore what is known about relapse risk and relapse management while considering emerging pathogenic and therapeutic paradigms.